Kad Hari Raya - Omar, Mokhtar; Abdullah, Orchid; Mokhtar, Nur Shalina; Mokhtar, Md. Nor Shareen; Mokhtar, Md. Nor Shafri; Mokhtar, Nur Shafinaz (Nil, 1990)
Kad ucapan hari raya yang diutuskan kepada Profesor Diraja Ungku Abdul Aziz daripada Hj. Mokhtar Hj. Omar, Hjh. Orchid bt. Abdullah, Nur Shalina, Md. Nor Shareen, Md. Nor Shafri dan Nur Shafinaz